Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1111/hel.12714
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antibiotic resistance on Helicobacter pylori eradication efficacy: A systematic review and meta‐analysis

Abstract: BackgroundThe occurrence of antibiotic‐resistant strains has been rapidly increasing due to the wide use of antibiotics. To evaluate the current effects of antibiotic resistance on Helicobacter pylori eradication efficacy, we conducted this systematic review and meta‐analysis.MethodsLiterature searches were conducted in the following databases: PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials. Statistical analysis was performed using STATA version 12.0 (StataCorp LP, College Station, TX, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 97 publications
0
48
0
3
Order By: Relevance
“…Probiotics, although helpful in alleviating negative symptoms associated with H. pylori antibiotic therapies, when used as a monotherapy have a low curability rate [ 16 ]. This has contributed to the situation in which antibiotics are the only accepted form of combating H. pylori , which in turn conditions the growing resistance of this microorganism to these medications [ 17 ]. The aforementioned phenomenon is exacerbated additionally by the narrow spectrum of antibiotics that are used to treat H. pylori infections (amoxicillin [AMX], clarithromycin [CLR], tetracycline [TET], metronidazole [MTZ], levofloxacin [LEV], and rifabutin [RIF]) [ 6 , 7 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics, although helpful in alleviating negative symptoms associated with H. pylori antibiotic therapies, when used as a monotherapy have a low curability rate [ 16 ]. This has contributed to the situation in which antibiotics are the only accepted form of combating H. pylori , which in turn conditions the growing resistance of this microorganism to these medications [ 17 ]. The aforementioned phenomenon is exacerbated additionally by the narrow spectrum of antibiotics that are used to treat H. pylori infections (amoxicillin [AMX], clarithromycin [CLR], tetracycline [TET], metronidazole [MTZ], levofloxacin [LEV], and rifabutin [RIF]) [ 6 , 7 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, since the use of fluoroquinolones has spread for urinary and respiratory infection, and considering that cross-resistance among fluoroquinolones may occur, a rapid rise in resistance to levofloxacin has taken place, with rates close to 40% in some reports [ 11 ]. This rise may have a relevant impact on eradication rates: a meta-analysis showed that successful eradication was achieved in 91.5% of sensitive strains and only 75% of resistant strains [ 12 ]. For levofloxacin, mutations in the gyrase A ( gyrA ) gene are responsible for antibiotic resistance [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of antibiotic resistance is the most common cause of eradication failure (Zou et al, 2020). In China, the rate of H .…”
Section: Discussionmentioning
confidence: 99%
“…The acquisition of antibiotic resistance is the most common cause of eradication failure (Zou et al, 2020). In China, the rate of H. pylori resistance to different antibiotics is generally high, with a clear difference among regions and populations (Ji et al, 2016;Liu et al, 2019;Tong et al, 2015;Zhang et al, 2015).…”
Section: Ta B L E 1 Baseline Characteristics For the Two Groups Of Pamentioning
confidence: 99%